Modeling of Dirac voltage for highly p-doped graphene field-effect transistor measured at atmospheric pressure - Muhamad Amri Ismail; Khairil Mazwan Mohd Zaini; Mohd Ismahadi Syono (Institute of Advanced Engineering and Science, 2020)
In this paper, the modeling approach of Dirac voltage extraction of highly p-doped graphene field-effect transistor (GFET) measured at atmospheric pressure is presented. The difference of measurement results between atmospheric and vacuum pressures was analyzed. This work was started with actual wafer-scale fabrication of GFET with the purposes of getting functional device and good contact of metal/graphene interface. The output and transfer characteristic curves were measured accordingly to support on GFET functionality and suitability of presented wafer fabrication flow. The Dirac voltage was derived based on the measured output characteristic curve using ambipolar virtual source model parameter extraction methodology. The circuit-level simulation using frequency doubler circuit shows the importance of accurate Dirac voltage value to the device practicality towards design integration.